Offshoring and labor markets in developing countries - Arnab K. Basu; Nancy H. Chau (IZA World of Labor, 2022)
Developing countries are often seen as unquestionable beneficiaries in the phenomenal rise of global value chains in international trade. Offshoring-the cross-border trade in intermediate goods and services which facilitate country-level specialization in subsets of production tasks-enables an early start in global trade integration even when the requisite technology and knowhow for cost-effective production from scratch to finish are not yet acquired. A growing economics literature suggests a more nuanced view, however. Policymakers should be mindful of issues related to inequality across firms and wages, labor standards, and effects of trade policy.
Keywords: F63; O1; F6; 330; offshoring; globalization; labor markets in developing countries